Análise de gênero e raça em documentos educacionais de domínio público - JOEL PEREIRA CIRQUEIRA (2023)
The National Common Curricular Base (BNCC) is a curriculum guideline that became law in 2022 for basic education in Brazil. Due to the relevance of this document, this research sought to understand how gender and race issues are addressed in it, as well as to defend the present performative properties of the document. The BNCC emerged in a sensitive period of Brazilian history, shortly after the 2016 coup, the 2018 presidential elections and the emergence of the controversial "gender ideology". In this context, the present research adopted a social constructionist perspective to analyze how gender and race are represented in the three versions of the High School BNCC of 2015, 2016 and 2017. The research was conducted with a qualitative approach, based on a critical analysis of the BNCC. In addition, the historical analysis of the advances and setbacks of public education policies in relation to gender and race was presented as part of the study. The three versions of the BNCC were analyzed, and it was observed that the 2015 and 2016 BNCC more frequently addressed gender and race issues. On the other hand, the 2017 version showed a drop in the inclusion of these themes, with gaps and a deletion of the categories of gender and race in the skills and theoretical foundation of the document.